2021
DOI: 10.9744/jti.23.2.93-100
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Shrinkage and Stockouts in a Food Retail Store

Pedro Alexandre Marques,
André Mendes De Carvalho

Abstract: Lean thinking is transforming the traditional way of a retail business operates to new and more effective practices. In particular, the food retail business is facing previously unseen challenges which require daily operational excellence to meet them with success. Low productivity, high variability in task completion, lack of work planning should be faced with daily relentless improvement actions. Kaizen, the continuous improvement pillar of Lean, needs to be seen not only as a methodology but also as a philo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Considering the findings identifying stock spoilage as the biggest contributor to profitability loss, this study is in line with that of a study investigating stock shrinkage and stockouts in retail stores wherein Marques and De Carvalho (2021) revealed that stock spoilage is one of the largest contributors of stock shrinkage. Results explain the financial losses retailers suffer because of expired stock.…”
Section: Multiple Regression Analysessupporting
confidence: 88%
“…Considering the findings identifying stock spoilage as the biggest contributor to profitability loss, this study is in line with that of a study investigating stock shrinkage and stockouts in retail stores wherein Marques and De Carvalho (2021) revealed that stock spoilage is one of the largest contributors of stock shrinkage. Results explain the financial losses retailers suffer because of expired stock.…”
Section: Multiple Regression Analysessupporting
confidence: 88%
“…OSA ensures that products sought by consumers are present on the shelf and in a saleable condition, whereas outof-stock (OOS) refers to the unavailability of specific products (Marques & Carvalho 2021;Bottani et al 2017). In this study, OOS was considered as an indicator of poor OSA.…”
Section: On-shelf Availability (Osa)mentioning
confidence: 99%
“…Phantom stock, a negative form of OSA, occurs when the inventory tracking system indicates the presence of a product that is no longer physically available. The reasons for a product not being visible on the shelf include being in a consumer's cart but not purchased, out of stock, or stolen (Marques & Carvalho 2021;Milella et al 2020). Previous research has identified various dimensions of stock availability, OSA as determinants of retailer firm performance (FP) (Schleper et al 2021;Tarigan et al 2020;Avlijas et al 2018;Moussaoui et al 2016).…”
Section: On-shelf Availability (Osa)mentioning
confidence: 99%